An umbrella review of the evidence associating diet and cancer risk at 11 anatomical sites - Nikos Papadimitriou (Nature Portfolio, 2021)
Diet and food intake have been associated with a risk of developing different types of cancer but individual nutritional epidemiology studies are prone to inherent bias. Here, the authors perform an umbrella review of meta-analyses of observational studies and show the level of evidence for associating food and nutrients to cancer risk.